Continuous Latent Spaces Sampling for Graph Autoencoder - Zhongyu Li; Geng Zhao; Hao Ning; Xin Jin; Haoyang Yu (Applied Sciences, 2023)
This paper proposes colaGAE, a self-supervised learning framework for graph-structured data. While graph autoencoders (GAEs) commonly use graph reconstruction as a pretext task, this simple approach often yields poor model performance. To address this issue, colaGAE employs mutual isomorphism as a pretext task for a continuous latent space sampling GAE (colaGAE). The central idea of mutual isomorphism is to sample from multiple views in the latent space and reconstruct the graph structure, with significant improvements in terms of the model’s training difficulty. To investigate whether continuous latent space sampling can enhance GAEs’ learning of graph representations, we provide both theoretical and empirical evidence for the benefits of this pretext task. Theoretically, we prove that mutual isomorphism can offer improvements with respect to the difficulty of model training, leading to better performance. Empirically, we conduct extensive experiments on eight benchmark datasets and achieve four state-of-the-art (SOTA) results; the average accuracy rate experiences a notable enhancement of <semantics>0.3%</semantics>, demonstrating the superiority of colaGAE in node classification tasks.